Athens besieged: Greek and Ottoman perceptions of shifting space during the Greek Revolution of 1821 - Panagiotis C. Poulos; Elias Kolovos (Journal of Greek Media & Culture, 2021)
This article explores aspects of the quotidian history of space in the Greek Revolution of 1821, using as a case study the transitional events of the siege of the Acropolis by the Ottoman army in 1826 and the recapturing of the city of Athens. Through a thorough study of space as embodied knowledge grounded in the dynamic interaction between humans and material culture, it identifies the shifts in the Athenian landscape during this period. Its findings are based on primary textual and visual sources pertaining to warfare, which are juxtaposed to the Greek and Ottoman emerging official perceptions of the significance of the city of Athens as a political and imaginary objective. The article deploys a phenomenological analysis of space that foregrounds the everyday experiential dimensions and is highly relevant in understanding the ideological and political complexities and implications of the shifting spatialities of the revolutionary period.